Fast-Track Surgery in Intestinal Deep Infiltrative Endometriosis. Issue 4 (October 2017) - Pissetti, Viviane C.; Nunes, Rodrigo D.; Zomer, Monica T.; Kondo, William
Fast-track (FT), also known as enhanced recovery after surgery (ERAS), is an integrated management of patients undergoing surgery, which is focused on optimal recovery and improvement of the overall quality of care. Minimally invasive surgery is the gold standard to diagnose and treat endometriosis, and its beneficial role within the FT program was reviewed. A search was performed for recent medical literature regarding the findings of the FT approach applied to intestinal deep infiltrative endometriosis surgery. This pathway comprises a diverse number of procedures arranged in preoperative, intraoperative, and postoperative settings. Evidence-based findings in randomized clinical trials have repeatedly shown that these protocols lead to enhanced recovery after surgery, reduced morbidity and mortality with a reduction in postoperative complications, and with readmission rates similar to conventional regimes.